Returning Nicholas - DeSaix, Deborah Durland (New York : Farrar Straus Giroux, 1995)
A young girl who loves horses takes a magical ride on a carousel.
School Library Journal
Publisher's Weekly
Kirkus Review
2.7
K-3
Keywords: Merry-go-round -- Fiction; Horses -- Fiction; Merry-go-round -- Fiction; Horses -- Fiction